P182 Describing long-term outcomes and the association with both receiving a diagnosis and time to diagnosis in adults presenting with breathlessness: a UK retrospective study using electronic healthcare records. (11th November 2022) - Karsanji, U; Lawson, CA; Bottle, A; Doe, G; Khunti, K; Quint, JK; Petherick, E; Steiner, MC; Evans, RA
Abstract : Introduction: Patients with chronic cardiorespiratory diseases commonly present with chronic breathlessness and there are well-described delays in diagnosis. The impact of delays to diagnosis in adults presenting with breathlessness is unknown. We therefore investigated the association of receiving a diagnosis or not, and time to diagnosis, on all-cause mortality in adults presenting with breathlessness. Method: Adults with a first-recorded code for breathlessness (index date) and subsequent coded diagnosis between 2007 and 2017 were included from a UK primary care database (CPRD-GOLD). Cox regression (HR [95% CI]) was used to determine the association of receiving a relevant diagnosis or not on 2-year outcome of all-cause mortality. Time-zero was set at date of diagnosis, and a landmark date of 2-years after index date was set for adults who did not receive a relevant diagnosis. For adults who received a diagnosis, the effect of time to diagnosis on mortality was investigated (time to diagnosis <6 months as reference vs 6–24 months and >24 months). Models were adjusted for sex, age, deprivation, body mass index, smoking, ethnicity, no. of comorbidities, and prior hospital admissions. Results: 101369 adults had a first-recorded code of breathlessness, of whom 66909 (66%) received and 34460 (34%) did not receive a diagnosis: mean (SD) age 57 (16) vs 49 (16) years, 38% vs 48% never smokers, 15% vs 28% no comorbidities, respectively. Adults who received a diagnosis had a higher risk of 2-year all-cause mortality (3.11 [2.43–3.98]) compared with those without a diagnosis. In adults who received a diagnosis, time to diagnosis was positively associated with risk of mortality (6–24 months 2.50 [1.81–3.46]; >24 months: 12.40 [9.35–16.50]). Figure 1 shows an unadjusted 2-year survival curve for all-cause mortality. Conclusion: Adults who received a relevant diagnosis for breathlessness had a higher risk of mortality within two years compared with those who did not receive a diagnosis. In those with a diagnosis, waiting beyond six months for a diagnosis was associated with worse survival.